Investigated stiffness of high performance superconductivity with nanoceria incorporated into polycrystalline magnesium diboride - Yarub, Al - Douri; Ghairabeh, M.; Albiss, B. A.; Ali Hussain, Reshak, Prof. Dr. (The Institution of Engineering and Technology, 2013)
Link to publisher's homepage at http://www.theiet.org/